Arthrogryposis in Murrah buffaloes in southern Brazil - Schild,Ana Lucia (2003)
Congenital arthrogryposis is described in a Murrah buffalo herd. The disease was characterized by curvature and multiple articular rigidity of the hindlimbs or of all limbs without associated defects except for one case of brachygnatia. Histologically there was reduction of motor neurons from the ventral horns of the spinal cord and hypoplasia of the limb muscles. Analysis of the herd breeding records suggests that the disease is genetically transmitted by an autosomal recessive trait.